On the Problem of Classification of the Source Base of the Personality Research - Larysa Smolinchuk (Pedagogical Discourse, 2013)
The source base of the personality research, which includes: autobiographies, characteristics, profiles, scientific and creative records, memoirs and diaries of an educator himself and other people regarding personality life activities; official personal documents (birth certificates, marriage certificates, education documents, memories, photographs); property and business documents that allow to determine the influence of such factors as health or financial position of a personality on his life activities; private correspondence, reviews on educational and scientific activity of a personality, is considered in the article.